2021
DOI: 10.47371/mycosci.2021.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Strong primer bias for <i>Tulasnellaceae</i> fungi in metabarcoding: Specific primers improve the characterization of the mycorrhizal communities of epiphytic orchids

Abstract: Primer bias toward Tulasnellaceae fungi during PCR is a known issue with metabarcoding analyses for the assessment of orchid mycorrhizal communities. However, this bias had not been evaluated for the fungal communities of epiphytic orchids, which account for 69% of all orchid species diversity. We compared the mycorrhizal communities detected using two primer pairs, a fungal universal primer pair (ITS86F/ITS4) and Tulasnella-specific primer pair (5.8STulngs/ITS4-Tul2), using a mock community of fungal isolates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 42 publications
(70 reference statements)
0
20
0
Order By: Relevance
“…Generally, it is accepted that orchids with high mycorrhizal specificity are most likely to be rare due to high dependency on OMF distribution in their natural habitats. In the case of V. falcata, its distributions were constricted from central to southern Japan with various types of phorophytes (Suetsugu et al 2015;Rammitsu et al 2019Rammitsu et al , 2021. Accordingly, V. falcata has high phenotypic variation even for wild plants across Japan, causing such extensive association to be beneficial to the plant for distribution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, it is accepted that orchids with high mycorrhizal specificity are most likely to be rare due to high dependency on OMF distribution in their natural habitats. In the case of V. falcata, its distributions were constricted from central to southern Japan with various types of phorophytes (Suetsugu et al 2015;Rammitsu et al 2019Rammitsu et al , 2021. Accordingly, V. falcata has high phenotypic variation even for wild plants across Japan, causing such extensive association to be beneficial to the plant for distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that vandaceous orchids-especially those of subtribe Aeridinae-mainly associated with Ceratobasidium, proven by metabarcoding and seed germination results (Otero et al 2002;Yukawa et al 2009;Hoang et al 2017;Mújica et al 2018;Rammitsu et al 2019;Kendon et al 2020). Although Ceratobasidium strains have also been isolated from V. falcata (Rammitsu et al 2021), mycobionts for seed germination have never been reported. Thus, this study analyzed the whole fungal community in seeds and root samples of V. falcata using amplicon sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps because of the use of an additional specific primer pair, Tulasnellaceae were the most abundant OMF in nearly all orchid species. However, the need to use specific primers to amplify this family is largely acknowledged and has been recently demonstrated by Rammitsu et al (2021). Tulasnellaceae and Serendipitaceae were both represented by numerous OTUs whereas only three OTUs of Ceratobasidiaceae were detected, only one being frequent, suggesting that Ceratobasidiaceae might be rarer in these epiphytic rainforest habitats (Martos et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, the experimental approach of using two primers may have distorted these comparative results regarding the three spatial classes of fungal communities. Different primers have preferences for various taxa, and this may introduce systematic bias into the results [68,69]. This limitation implies that results concerning comparisons between plant roots and soil need to be interpreted cautiously.…”
Section: Discussionmentioning
confidence: 99%